EXAMINING THE ADVANTAGES OF STUDYING IN E-LEARNING DISTANCE MODE BY PRISONERS - Mahlangu Vimbi PETRUS (Social Sciences and Education Research Review)
The purpose of the study was to examine the advantages of studying in e-learning distance mode by prisoners. The paper's central claim is that, despite their severe living conditions, inmates who are committed to their education cannot have their education impeded by prison walls. This research was carried out in a prison in Namibia. This study was qualitative in nature, utilizing interviews as a means of data collecting while adhering to an interpretive paradigm. The analysis was conducted thematically. Imprisonment presents prisoners with increased opportunities for self-improvement. However, studying while incarcerated, especially remotely, is exceedingly challenging for prisoners.